2017
DOI: 10.1002/cphc.201601445
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Cation–Solvent and Cation–Anion Interactions in Imidazolium Ionic Liquids with Polar Aprotic Solvents

Abstract: The subtle interplay between ion solvation and association was analyzed in mixtures of imidazolium-based ionic liquids (ILs) with polar aprotic solvents. A site-specific pattern of cation-solvent and cation-anion interactions was disclosed by a careful analysis of the H and C NMR chemical shift dependence of the mixture composition. It was established that the less polar but more donating γ-butyrolactone is more prone to establish H-bonds with the imidazolium-ring hydrogen atoms of the IL cations than propylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“… 37 Even though acetonitrile is rather similar to DMSO in polarity, it does not seem to break ionic aggregates into separate ions, apparently due to the poorer hydrogen-bond accepting abilities. 45 , 48 50 Varying degrees of dissociation of the [C4mim]-based 35 , 51 , 52 and ammonium-based 41 ILs in acetonitrile solution were, however, reported. At low concentrations in nonpolar solvents, ILs tend to form supramolecular aggregates, 35 , 44 , 51 , 53 55 although lone contact ion pairs were seen to be the dominant association pattern for some ILs in chloroform 47 and dichloromethane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 37 Even though acetonitrile is rather similar to DMSO in polarity, it does not seem to break ionic aggregates into separate ions, apparently due to the poorer hydrogen-bond accepting abilities. 45 , 48 50 Varying degrees of dissociation of the [C4mim]-based 35 , 51 , 52 and ammonium-based 41 ILs in acetonitrile solution were, however, reported. At low concentrations in nonpolar solvents, ILs tend to form supramolecular aggregates, 35 , 44 , 51 , 53 55 although lone contact ion pairs were seen to be the dominant association pattern for some ILs in chloroform 47 and dichloromethane.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the low-concentration aqueous solutions of ILs behave as traditional electrolytes, where ions are virtually completely solvated, , although in some instances ion pairing was detected even at rather low concentrations of the IL. , Dimethyl sulfoxide, DMSO, has also demonstrated the capability of breaking ionic aggregates into separate ions, , but, here too, some ILs have displayed slight association at high dilutions. , Remarkably, however, higher-order supramolecular ionic clusters were found to persist at rather low concentrations of [C4mim]­[Cl] IL in DMSO . Even though acetonitrile is rather similar to DMSO in polarity, it does not seem to break ionic aggregates into separate ions, apparently due to the poorer hydrogen-bond accepting abilities. , Varying degrees of dissociation of the [C4mim]-based ,, and ammonium-based ILs in acetonitrile solution were, however, reported. At low concentrations in nonpolar solvents, ILs tend to form supramolecular aggregates, ,,, although lone contact ion pairs were seen to be the dominant association pattern for some ILs in chloroform and dichloromethane. , However, the dissociation of [C4mim]­[Cl] ion pairs into separate ions in solutions of chloroform and carbon tetrachloride has been observed very recently. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marekha et al investigated the effects of aprotic polar solvents, such as propylene carbonate and γ-butyrolactone, on imidazolium based ILs by measuring variations in NMR chemical shifts. They observed a decrease in the strength of the interionic interactions in the presence of those solvents . Additionally, computational studies have shown that generally stronger hydrogen bonding is observed in IL systems with polar and protic solvents than with aprotic solvents. , Thus, there have been many spectroscopic and computational studies of interactions for imidazolium based ILs, but these studies primarily focused on ILs with very weakly basic anions that do not have the ability to chemically react with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics determine the properties and structure of pure ILs but also have a large effect when mixing with molecular solvents (MSs) [4][5][6][7]. Intermolecular forces between ILs and MSs are largely complex [810], even with the appearance of competition effects between the involved ions and molecules [11], because of their dependence on the protic or aprotic, polar or apolar, or hydrogen bonding ability of the MSs, and show remarkable changes with mixture composition, pressure and temperature [12][13][14][15]. These mechanisms of ILs-MSs interactions determine the macroscopic physicochemical properties of mixed fluids [1618], and thus, their possible application for several technologies at industrial level [1921].…”
Section: Introductionmentioning
confidence: 99%